2018
DOI: 10.1103/physrevfluids.3.013905
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the wake behind a rotating sphere

Abstract: The wake behind a sphere, rotating about an axis aligned with the streamwise direction, has been experimentally investigated in a low-velocity water tunnel using LIF visualizations and PIV measurements. The measurements focused on the evolution of the flow regimes that appear depending on two control parameters, namely the Reynolds number Re and the dimensionless rotation or swirl rate Ω, which is the ratio of the maximum azimuthal velocity of the body to the free stream velocity. In the present investigation,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
5
13
0
Order By: Relevance
“…However, the harmonic 2f a develops at the near wake, as observed in the spectrum of w , although its magnitude is weak in comparison with the main peak. Interestingly, if the sphere's rotation frequency is denoted as f r , the ratio f a /f r 1 3 , which agrees well with previously reported values by Pier (2013) and Skarysz et al (2018) for low Ω.…”
Section: Frequency Analysissupporting
confidence: 91%
See 4 more Smart Citations
“…However, the harmonic 2f a develops at the near wake, as observed in the spectrum of w , although its magnitude is weak in comparison with the main peak. Interestingly, if the sphere's rotation frequency is denoted as f r , the ratio f a /f r 1 3 , which agrees well with previously reported values by Pier (2013) and Skarysz et al (2018) for low Ω.…”
Section: Frequency Analysissupporting
confidence: 91%
“…First, it is observed that, for Ω 1.4, m = 1 (m 1 ) and m = 0 (m 0 ) symmetries are the most energetic at the wake. In particular, the enstrophy of mode m 0 grows monotonously with Ω until it reaches a saturated value around 1.4, in line with the experimental results of Skarysz et al (2018). Therefore, the initial growth in ε(m 0 ) during the periodic and quasi-periodic regimes can be attributed to the linear addition of cyclonic vorticity due to the rotation of the sphere.…”
Section: Fourier Azimuthal Decompositionsupporting
confidence: 86%
See 3 more Smart Citations